Astrochemical evolution along star formation: overview of the IRAM Large Program ASAI. Issue 4 (14th April 2018) - Lefloch, Bertrand; Bachiller, R; Ceccarelli, C; Cernicharo, J; Codella, C; Fuente, A; Kahane, C; López-Sepulcre, A; Tafalla, M; Vastel, C; Caux, E; González-García, M; et al.
Abstract: Evidence is mounting that the small bodies of our Solar system, such as comets and asteroids, have at least partially inherited their chemical composition from the first phases of the Solar system formation. It then appears that the molecular complexity of these small bodies is most likely related to the earliest stages of star formation. It is therefore important to characterize and to understand how the chemical evolution changes with solar-type protostellar evolution. We present here the Large Program 'Astrochemical Surveys At IRAM' (ASAI). Its goal is to carry out unbiased millimetre line surveys between 80 and 272 GHz of a sample of 10 template sources, which fully cover the first stages of the formation process of solar-type stars, from pre-stellar cores to the late protostellar phase. In this paper, we present an overview of the surveys and results obtained from the analysis of the 3 mm band observations. The number of detected main isotopic species barely varies with the evolutionary stage and is found to be very similar to that of massive star-forming regions. The molecular content in O- and C-bearing species allows us to define two chemical classes of envelopes, whose composition is dominated by either (a) a rich content in O-rich complex organic molecules, associated with hot corino sources, or (b) a rich content in hydrocarbons, typical of warm carbon-chain chemistry sources. Overall, a high chemical richness is found to be present already in the initial phases of solar-type star formation.